2016
DOI: 10.1002/jbmr.2806
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and 3-Phosphoinositide-Dependent Kinase 1 (PDK1)-Related Kinome in Pagetic Osteoclasts

Abstract: In Paget's disease of bone (PDB), a major contributory factor are osteoclasts (OCs) that are larger, more numerous, resistant to apoptosis, and hyperactive. The aim of this human in vitro study was to identify kinase cascades involved in the OC phenotype and to determine their impact on downstream processes. Basal phosphorylation levels of Akt and ERK were found to be elevated in PDB OCs. Given our previous findings that 3-phosphoinositide-dependent protein kinase 1 (PDK1) associates with the crucial adaptor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…As inclusion bodies in pagetic osteoclasts resemble the sequestosome-1 or SQSTM1/p62 aggregates observed in diseases involving defective autophagy, the pathogenesis of PDB possibly involves the impairment of autophagy [ 86 ]. In previous studies, defects in autophagy flux were observed in PBD osteoclasts or Cos-1 cells harboring a PDB-associated p62 mutation, suggesting accumulation of non-degradative autophagosomes [ 87 , 88 ]. The activation of TBK1 (TANK binding kinase) and TBK1-induced IL-6 production may also contribute to the generation of PDB osteoclasts [ 89 ].…”
Section: Rab Gtpases In Human Bone Diseasesmentioning
confidence: 99%
“…As inclusion bodies in pagetic osteoclasts resemble the sequestosome-1 or SQSTM1/p62 aggregates observed in diseases involving defective autophagy, the pathogenesis of PDB possibly involves the impairment of autophagy [ 86 ]. In previous studies, defects in autophagy flux were observed in PBD osteoclasts or Cos-1 cells harboring a PDB-associated p62 mutation, suggesting accumulation of non-degradative autophagosomes [ 87 , 88 ]. The activation of TBK1 (TANK binding kinase) and TBK1-induced IL-6 production may also contribute to the generation of PDB osteoclasts [ 89 ].…”
Section: Rab Gtpases In Human Bone Diseasesmentioning
confidence: 99%
“…Moreover, inhibition of autophagy by mTORC1 promoted OC survival and RANKL-induced formation and activation of OCs [ 51 , 52 ]. Dysfunctional autophagy has also been identified in the OC phenotype of Paget's bone disease, in which defects in autophagy induction and clearance of autophagosomes have been observed [ 53 ], and activated autophagy in OCs was associated with rheumatoid arthritis [ 54 ].…”
Section: Roles Of Rab Gtpases and Their Regulators In Autophagymentioning
confidence: 99%
“…NONMMUT000375.2 and NONMMUT071578.2 may bind to miR‐28a‐5p, and Pdk1 is a direct target of miR‐28a‐5p. It was demonstrated a regulatory role in osteoclast stimulatory pathways (McManus et al, 2016). In this case, the up‐regulated expressed NONMMUT000375.2 should increase the expression of Pdk1 and thereby enhanced osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%